PEMENUHAN HAK-HAK ASASI ANAK TENAGA KERJA INDONESIA DI PERKEBUNAN SAWIT DI WILAYAH TAWAU, SABAH, MALAYSIA - Sholina, Cicilia Anggi (UI Scholars Hub, 2022)
Protection of children is a guarantee that has been agreed globally. The form of protection that can be provided is to ensure that children's rights are fulfilled wherever they are, including when they are not in Indonesia. Children of Indonesian Migrant Workers (PMI) experience multiple vulnerabilities, especially when children have to be born and live in the country where PMI works. The most obvious problem is the emergence of stateless children. Child without a birth certificate or citizenship certificate, has limited access to basic needs and government services. Guarantees for the protection of children has become the responsibility of all parties. So, through a qualitative approach and in-depth interview methods, the authors try to see to what extent PMI's role and efforts as parents, the state through the Indonesian Consulate (KRI), and the company where PMI works in fulfilling children's rights in the Palm Oil Plantations in the Tawau Region, Sabah, Malaysia. The authors' findings show that various positive efforts have been made by the company and KRI in Tawau to fulfill children's rights to education, health, and other needs related to the life of children's growth and development. However, it was found that the awareness of parents in particular to fulfill children's rights to education is still low so that there are still children who have to work with their parents. Meanwhile, educational facilities and infrastructure in the form of Community Learning Center (CLC) has continue to be developed by the corporation, starting from the teachers to the curriculum. Another challenge faced is the reluctance of PMIs who enter illegally to report themselves and their families, so that outreach efforts to PMI's children are still not optimal. This study shows that the fulfillment of the rights of PMI children can be done better with collaboration and synergy between parties. The combination of awareness and willingness of parents to open children's access to services along with optimized facilities from the company and KRI can contribute to better fulfillment of children's rights.